Identity, personhood and power : a critical analysis of the principle of respect for autonomy and the idea of informed consent, and their implementation in an androgynous and multicultural society - Rossouw, Theresa Marie (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2012.